Tradisi Devosional Semana Santa dan Tuan Ma Di Larantuka Ditinjau Dari Hukum Kebiasaan KHK Kan. 25-26 - Yohanes Mba Malo Sali; Felix Lawa; Yohanes Endi (Journal New Light, 2024)
The devotional traditions of Semana Santa and Tuan Ma in Larantuka, which have been ongoing for over five centuries, constitute profound and integral religious practices for the local Catholic community. Examined from the perspective of customary law in the Code of Canon Law (CCL) Canons 25-26, this analysis aims to evaluate whether these traditions meet the criteria to be recognized as valid customs with legal force. In conducting this assessment, the research involves examining the extensive history of these traditions, comparing their practices with the requirements set forth in Canons 25 and 26, and analyzing the support from ecclesiastical authorities and local government. The results indicate that the Semana Santa and Tuan Ma traditions meet the criteria established in CCL Canons 25-26, involving the continuous participation of the entire community for over five centuries. Formal support from the Bishop of Larantuka and cooperation with local government agencies strengthen the legitimacy of these traditions, ensuring that their practices are respected and preserved within the framework of ecclesiastical law. Thus, this analysis confirms that the devotional traditions of Semana Santa and Tuan Ma are not only significant cultural heritage but also integral parts of customary law within the Catholic Church, in accordance with CCL Canons 25-26.